(untitled) (Homoeopathy for All, 2022)
‘Teaching’ and ‘Research’ are two important domains of academia which need promotion and growth independently for the benefit of homoeopathic professionals of all categories. Most of the academicians believe in research- informed teaching, since quality research is essential for teaching of high standard. The research activities of the teaching faculty increase knowledge currency, credibility, competence in supervision and motivation. It is an established fact that research- informed teaching is essential for high quality teaching. Similarly, quality of research methodology and outcomes depends upon the educational background of the researchers. The link between teaching and research cannot be established automatically. Rather, an integrated teaching and research environment has to be created in the campuses of educational and research institutions, with the efforts of the policy makers, statutory and regulatory bodies, universities and support of the teaching faculty with whole hearted cooperation of the students – the ultimate beneficiaries